Low Infection Rate after Tumor Hip Arthroplasty for Metastatic Bone Disease in a Cohort Treated with Extended Antibiotic Prophylaxis - Werner H. Hettwer; Peter Frederik Horstmann; Thea Bechmann Hovgaard; Tomas Andreas Grum-Scwensen; Michael M. Petersen (Advances in Orthopedics)
Background. Compared to conventional hip arthroplasty, endoprosthetic reconstruction after tumor resection is associated with a substantially increased risk of periprosthetic joint infection (PJI), with reported rates of around 10% in a recent systematic review. The optimal duration of antibiotic prophylaxis for this patient population remains unknown. Material and Methods. To establish the infection rate associated with prolonged antibiotic prophylaxis in our department, we performed a retrospective review of all adult patients who underwent endoprosthetic reconstruction of the proximal femur after tumor resection for metastatic bone disease during a 4-year period from 2010 to 2013 (n=105 patients). Results. Intravenous antibiotic prophylaxis was administrated for an extended duration of a mean of 7.4 days. The overall infection rate was 3.6% (4/111 implants), infection free survival was 96% at 2 years, and the risk of amputation associated with infection was 25% (1/4 patients). Discussion. Preemptive eradication of bacterial contamination may be of value in certain clinical situations, where the risk level and consequences of implant-associated infection are unacceptable. Our findings suggest that extended postoperative antibiotic prophylaxis may reduce the risk of PJI in patients undergoing tumor resection and endoprosthetic replacement for metastatic bone disease associated impending or de facto pathologic fractures of the proximal femur.